Diseño e implementación de guías de usuarios para los procesos de mantenimiento preventivo y correctivo de computadores en el laboratorio de redes y mantenimiento en la Universidad Técnica de Cotopaxi extensión La Maná - Avalos Mera, Winton Wladimir (2015)
This project describes a plan for preventive and corrective maintenance of computers, server, router and switch networks lab labotory of the Technical University of Cotopaxi extension La Maná and how can develop a proper management based on the need to keep always functional for students to develop its practices without alteration in addition to promoting research as a means binding between the university and society.